Pangkalan Udara Adi Sutjipto Yogyakarta: Perkembangan Fungsi Lapangan Udara Dari Militer Menjadi Penerbangan Sipil Tahun 1964-2004 - Anjani, Nadya Putri; Utami, C. Santi Muji (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2020)
In the 1964-2000s, along with the development and advancement of air transportation facilities was a result of advances in science and technology one of which was the development of the function of military air base used in conjunction with civil airports. The existence of Yogyakarta Adisutjipto Airport in its development experienced a dynamic that could scratch historical ink not only for AURI, but also the history of the Indonesian people. This research uses historical research methods. Beginning with collecting sources, also known as heuristics. The next step is source criticism, not only external criticism about the form of the archive or source with what the writer later narrates. Furthermore, the writer does the last step called historiography or writes what has been obtained from the source search. The result showed that the role of Adisutjipto Airport in 1940s to 2000s was quite large. Especially, in around 1964, Adisutjipto Airport became a joint military civil airport which had an impact on the increasing rate of the regional economy. In further development, Adisutjipto Airport became an international airport in 2004, because the flow of domestic and foreign tourists through the airport has increased every year. The significant impact was born due to selling tourism sector in Yogyakarta which is supported by Adisutjipto Airport.